👤

40 punctee!!
Rezolvati in R evuatia:
a) (x-1)^2+(x+2)^2-(x-2)(x+2)=24
b) (x-2)^2+(x+1)^2-(x-1)(x+1)=14


Răspuns :

a)
[tex] (x-1)^{2} + (x+2)^{2} -(x-2)(x+2)=24[/tex]

x²-2x-1²+x²+2*x*2+2²-x²-2²=24
x²-2x-1+x²+4x+4-x²-4=24(+x² cu -x² se reduc si da 0)(+4 cu -4 se reduc si da 0)
x²-2x+4x-1-24=0
x²+2x-25=0

b)
[tex]( x-2)^{2}+ (x-1)^{2} +(x-1)(x+1)=14 [/tex]

x²-2*x*2-2²+x²+2x+1²-x²+1²=14
x²-4x-4+x²+2x+1-x²+1=14(+x² cu -x² se reduc si da 0 )
x²-4x+2x+1+1-14=0
x²-2x-12=0

sper ca te-am ajutat
succes in continuare